A Study on the Body-Building Values of Daoyin Illustration in Light of Neurophysiology: 從神經生理學觀點探析馬王堆漢墓<導引圖>的健身價值 - HUANG, Ruixin; ZHUANG, Jie; HU, Qichen; SOONG, Xianxaing (Asian Journal of Physical Education & Recreation, 1999)
LANGUAGE NOTE | Document text in English; abstract also in Chinese. Daoyin Illustration, with 44 Daoyin postures unearthed from the Western Han Dynasty Tomb III at Mawangdui in Hunan Province, China, is the earliest body-building Illustration found by Chinese archaeologists. Other ancient Chinese sports of DaoyinShu, such as Wuqinxi, Baduanjin, Yijinjing and Taijiquan, were the results of evolution and development of Daoyin Illustration according to their dates of appearance and movements. The people in ancient times practised them, combining the movements of body and limbs with breathing and therapeutic treatment with keeping fit and motion with tranquility in order to keep the harmony between Yin and Yan. From the viewpoint of neurophysiology, the central nervous system (CNS) receives the inputs from all of the organs and tissues, which bring the information of changes in the external and internal environments. The information from contractions and stretches of muscles and tendons inputted by thicker afferent fibers can inhibit and adjust the activities of internal organs controlled by thinner nervous fibers. All inputs interact with the changes in external and internal environments and be in harmony with them. This is the process of the central integration. The value of Daoyin Illustration in building up health is to maintain the internal homeostasis through moderate movements of the body and limbs to affect the activities of the internal organs. 馬王堆漢墓<導引圖>是我國考古發現中時代最早的健身圖譜，共有四十四個術勢。從出現年代和動作結構分析，它的導引術如五禽戲、八段錦、易筋經、太極拳等是從<導引圖>繼承和演化而來。古人操練這些動作是通過肢體運動與呼吸結合，治療與健身結合，動靜相結合以求陰陽平衡。從神經生理學觀點來看，中樞神經系統接受來自所有組織與器官發來的衝動，這些衝動帶來了關於外環境變化和自體機能狀態即內環境變化的信息。體表下軟組織(特別是肌肉與肌腱的收縮和牽張所引起的)由較粗神經纖維的傳入電衝動，對於較細神經纖維所支配的內臟器官的活動有某種抑制與調節作用。各種信息在中樞神經系統內相互作用，相互制約，以確定最後的反射活動，使有機體適應體內外所發生的變化，以維持有機體與環境的平衡，這就是中樞整合過程。馬王堆漢墓<導引圖>所體現的健身價値就在於通過適當的肢體運動以影響內臟活動，調理機體內環境的穩定平衡。